QUALITY OF LIFE AND RELATIONSHIP BETWEEN FUNCTIONING AND SYMPTOMS OF FEMALE PATIENTS WITH BREAST CANCER BEFORE CHEMOTHERAPY IN A CANCER CLINIC AT YANGON, MYANMAR - Naung, Min Thu; Panza, Alessio (Journal of Ayub Medical College Abbottabad, 2020)
Background: Better quality of life (QOL) is associated with longer survival in cancer patients. This study evaluated the QOL and relationship between functioning and symptoms among female breast cancer patients before chemotherapy. Methods: Cross-sectional study was conducted by including 74 participants attending a cancer clinic. European Organization for Research and Treatment of Cancer Quality of Life Questionnaire(s)-Core30 was applied for assessing QOL. It was composed of three domains namely global health status/QOL, functioning (includes five categories) and symptoms (includes nine categories). Pearson correlation and multiple linear regression were performed to find the relationship between functioning and symptoms in participants. The study was approved by Institutional Review Board of Defence Services Medical Research Centre, Myanmar with approval number IRB/2018/34. Results: Global health status/QOL score was fair (61.8±20.1). Among the five categories of functioning, cognitive functioning score (83.6±19.8) was the highest and role functioning score (66.4±29.3) was the lowest. Among symptoms, insomnia score (29.3±30.7) was the highest and diarrhoea score (0.9±5.4) was the lowest. When Pearson correlation was performed, functioning and symptoms were negatively correlated. Fatigue had significant (p<0.001) moderate negative correlation with physical functioning, role functioning and emotional functioning, whereas pain with role functioning (p<0.001). When linear regression was performed, nausea & vomiting was the strongest predictor for impaired global health status/QOL (p<0.05), while fatigue was the strongest predictor for impairment in all five categories of functioning (p<0.05). Conclusion: Functioning and symptoms were negatively correlated in breast cancer patients. Nausea & vomiting and fatigue were the strongest predictors for impaired QOL. Keywords: Breast Cancer; Chemotherapy; Functioning; Symptoms; Quality of Life; QOL